A PROPOSAL TO COMPUTE A FAIR RECOVERABLE COMMON COST BY USING ACTUAL REVENUE AS A BASIS ÃâÃâ A CASE STUDY AT AN OIL AND GAS CONTRACTOR IN INDONESIA - SHINTA FONTY (NIM 29115441), DIAN
Oil and Gas is a business with a high factor of vulnerability, uncertainty, complexity and ambiguity conditions. With that condition, performing cost efficiency and control become the priority, especially to production companies to ensure the cost can be covered by its revenue. Under the PSC term, the calculation of cost, revenue and net income (revenue entitlement) must be performed separately between oil product and gas product. In accordance to PTK0059/2015, operating cost differentiated as Direct Cost (to oil or gas) and Common Cost (to both oil and gas). Common Cost in Saka hold 23% to 46% from total cost for year 2012 to 2016. This final project uses quantitative methodology to review whether the current scheme of Common Cost allocation which currently using the fixed POD Projected Revenue percentage of 55%:45% ratio is still providing a fair basis of computing recoverable common cost to both Contractor and Government. Further analysis performed by seeing the impact to ETBS of Kujung block and impact of actual revenue model to support Saka business strategy and accounting concept of matching cost against revenue. For analytical purposes, the two models use financial data of Kujung block from 2012 to 2016 from financial quarterly report (FQR), a report submitted to SKK Migas. The result of this final project shows the shifting of common cost allocated from gas to oil as the revenue of oil was dominant in 2012 to 2014. And in line with the increase of gas revenue in 2015 – 2016, there is a shifting of common cost allocated from oil to gas in these years. The net shifting from oil to gas of recovered cost from 2012 – 2016 is US$56,466,000. Implementing Actual Revenue Model support this final project objective for a fair and equitable result to both Contractor and Government as Contractor will receive the portion of FTP and the recovery of costs at current period. The Government will be able to collect Government Tax Entitlement from the remaining Gross Revenue after FTP and Operating Cost once Kujung block reach ETBS position. This means Government will receive more portion than 20% FTP component.